Effect of Surfactant Concentrations on the Properties of Sol-Gel Spin Coated GaN Thin Films - Amin, NurFahana Mohd; Sha, Shiong Ng (2016)
We report on the effects of different surfactant concentrations on the properties of gal lium nitride (GaN) thin films grown on si licon substrate by so l-gel spin coati ng method. The precursor so lution was prepared using gallium nitrate hydrate powder as starting material. ethano l, diethanolamine (DEA) and distilled water were used as so lvent and stabi lizer, respectively. DitTerent molar ratios of DEA to gallium nitrate hydrate (i.e. , 1: I, 2:1 and 3: I) were used. The crystal structure and orientation of the films were analyzed by X-ray diffraction technique (XRD). The XRD results revealed that a ll the deposited films with different surfactant concentrations have wurtzite structure and with GaN(002) preferred orientation. Field-emission scanning electron microscopy showed that GaN thin films with uniform and packed grain thin tilm were tormed. Energy dispersive X-ray spectroscopy show that the present of gallium, nitrogen, oxygen and si licon. The optical study was investigated by Fourier transform infrared spectroscopy and the transverse and longitudinal phonon modes of wurtzite GaN were clearly identified from the films prepared under various surfactant concentrations. All the results reveal that the concentration of surfactant plays an important role tor quality of GaN thin films.